2022
DOI: 10.1021/acssuschemeng.1c07897
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable CO2 Reduction on In2O3 with Exclusive CO Selectivity: Catalysis and In Situ Valence Band Photoelectron Spectral Investigations

Abstract: This study demonstrates a sustainable catalytic CO2 conversion to near 100% CO selectivity at ambient pressure on In2O3. Critically, high CO yield could be observed at the cost of undesired methanation, using a lower than stoichiometric amount of hydrogen in the feed; 1:1 and 1:0.67 CO2:H2 ratios exhibit 98–99.6% CO selectivity with 25–38% CO2 conversion between 773 and 873 K. CO2 and H2 conversion under steady-state conditions at 773–873 K suggests a 1:1 ratio of adsorbed reactants (with 1:0.67 CO2:H2 feed) o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 51 publications
0
7
0
1
Order By: Relevance
“…This is further supported by the IR gas-phase measurements, which show the presence of hydrogen-containing adsorbates on the surface after H 2 treatment (see Figure 2). In this context, in a previous near-ambient-pressure (NAP) UPS study on In 2 O 3 during rWGSR, it was shown that the temperature as well as the CO 2 :H 2 ratio have a strong influence on the valence region, [48] which is reflected in line broadening. This is in agreement with our findings that the surface is strongly influenced by the gas environment, where a greater CO 2 content leads to greater changes, which indicates the presence of carbonaceous adsorbates.…”
Section: Angewandte Chemiementioning
confidence: 95%
“…This is further supported by the IR gas-phase measurements, which show the presence of hydrogen-containing adsorbates on the surface after H 2 treatment (see Figure 2). In this context, in a previous near-ambient-pressure (NAP) UPS study on In 2 O 3 during rWGSR, it was shown that the temperature as well as the CO 2 :H 2 ratio have a strong influence on the valence region, [48] which is reflected in line broadening. This is in agreement with our findings that the surface is strongly influenced by the gas environment, where a greater CO 2 content leads to greater changes, which indicates the presence of carbonaceous adsorbates.…”
Section: Angewandte Chemiementioning
confidence: 95%
“…Furthermore, severe electron/hole recombination and slow surface reaction kinetics limit the photocatalytic performance. [5,6] Therefore, the focus of the current research is to design materials that can reduce the activation energy required for reduction reactions, increase the amount of photogenerated electrons, and accelerate the separation of electrons and holes to improve CO 2 reduction efficiency and product selectivity. [7,8] Among the developed photocatalysts, transition metal hydroxides, as noble-metal-free cocatalysts, are attractive because they are naturally abundant, cost effective, and have high CO 2 adsorption capacity.…”
mentioning
confidence: 99%
“…The Ce 3d spectrum consists of two multilayer states, which correspond to spin–orbit split Ce 3d 5/2 and Ce 3d 3/2 core holes. In the O 1s spectrum, three characteristic peaks are lattice oxygen (O l , 529.7 eV), carbon–oxygen bonds (C–O, 531.2 eV), and hydroxyl oxygen (O–H, 532.3 eV), respectively (Figure g). The similar characteristic peaks of Bi 4f, Ce 3d, and O 1s spectra can be observed in the control CeO 2 and Bi 2 O 3 samples (Figures S10 and S11). Thus, all of the above experimental results confirm the successful synthesis of CeO 2 , Ce-doped Bi 2 O 3 , and Bi 2 O 3 samples.…”
Section: Resultsmentioning
confidence: 53%